Are there conserved roles for the extracellular matrix, cilia, and junctional complexes in left‐right patterning?. Issue 6 (7th April 2014) - Collins, Michelle M.; Ryan, Aimee K.
Summary: Many different types of molecules have essential roles in patterning the left‐right axis and directing asymmetric morphogenesis. In particular, the relationship between signaling molecules and transcription factors has been explored extensively. Another group of proteins implicated in left‐right patterning are components of the extracellular matrix, apical junctions, and cilia. These structural molecules have the potential to participate in the conversion of morphogenetic cues from the extracellular environment into morphogenetic patterning via their interactions with the actin cytoskeleton. Although it has been relatively easy to temporally position these proteins within the hierarchy of the left‐right patterning pathway, it has been more difficult to define how they mechanistically fit into these pathways. Consequently, our understanding of how these factors impart patterning information to influence the establishment of the left‐right axis remains limited. In this review, we will discuss those structural molecules that have been implicated in early phases of left‐right axis development. genesis 52:488–502, 2014. © 2014 Wiley Periodicals, Inc.